Hair cortisol concentration and neurocognitive functions in preschool children at risk of developing attention deficit hyperactivity disorder. (September 2021) - Mann, Christopher; Schloß, Susan; Cosan, Alisa; Becker, Katja; Skoluda, Nadine; Nater, Urs M.; Pauli-Pott, Ursula
Abstract: Objective: Sex differences have been shown in the relation between hair cortisol concentration (HCC) and ADHD symptoms. As an extension of these findings, we analyze whether a child's sex modulates the associations between HCC and ADHD-related neurocognitive functions. Methods: A community-based sample of 122 children was tested at age 4–5 (T1) and 8 (T2) years. At T1 and T2, ADHD symptoms were assessed with clinical parent interviews and parent and teacher questionnaires. Neurocognitive functions (i.e. T1: inhibitory control, working memory (WM), T2: verbal and performance intelligence (IQ-p)) were assessed using (neuro-)psychological tests. At T1, HCC was analyzed in the most proximal 3 cm scalp hair segment using luminescence immunoassay. Results: Exclusively in boys, low HCC correlated with low WM and IQ-p. The sex-by-HCC interaction effect on WM was significant. In boys, HCC completely explained the links of ADHD inattention symptoms with WM and IQ-p, respectively. Conclusion: Results suggest a specific neurocognitive/endocrine profile in preschool boys at risk of developing ADHD, comprising hypocortisolism combined with memory and attention deficits. Highlights: Low HCC was found to be associated with ADHD in boys (HCC, hair cortisol concentration, ADHD, attention-deficit hyperactivity disorder). We analyzed links between HCC and neurocognitive functions (HCC, hair cortisol concentration). HCC was linked to WM, exclusively in boys (working memory). HCC completely explained the link between WM and ADHD inattention symptoms. Low HCC may indicate a specific neurocognitive profile in boys at risk of developing ADHD.